2019
DOI: 10.1016/j.devcel.2018.11.048
|View full text |Cite
|
Sign up to set email alerts
|

Neurog3-Independent Methylation Is the Earliest Detectable Mark Distinguishing Pancreatic Progenitor Identity

Abstract: Summary In the developing pancreas, transient Neurog3-expressing progenitors give rise to four major islet-cell types, α, β, δ, and γ; when and how the Neurog3+ cells choose cell-fate is unknown. Using single-cell RNAseq, trajectory analysis, and combinatorial lineage tracing, we showed here that the Neurog3+ cells co-expressing Myt1 (i.e., Myt1+Neurog3+) were biased towards β-cell fate; while those not simultaneously expressing Myt1 (Myt1-Neurog3+) favored α-fate. Myt1 manipulation only marginally affected α-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(58 citation statements)
references
References 81 publications
(115 reference statements)
3
54
0
Order By: Relevance
“…7F). This finding is in line with a recent study showing that Ngn3 + cells that express Myt1 are biased toward β-cell fate (Liu et al, 2019). The balance between the expression of Arx and Pax4 is the only currently known mechanism of endocrine cell subtype specification (Collombat et al, 2003(Collombat et al, , 2009.…”
Section: Stage-dependent Heterogeneity Of Eps Defines Endocrine Cellsupporting
confidence: 90%
“…7F). This finding is in line with a recent study showing that Ngn3 + cells that express Myt1 are biased toward β-cell fate (Liu et al, 2019). The balance between the expression of Arx and Pax4 is the only currently known mechanism of endocrine cell subtype specification (Collombat et al, 2003(Collombat et al, , 2009.…”
Section: Stage-dependent Heterogeneity Of Eps Defines Endocrine Cellsupporting
confidence: 90%
“…Therefore, in current cell replacement therapy research, endogenous alpha cells are considered to be important for β cell reprogramming. Recent studies have also shown that inhibiting DNA methylation in pancreatic progenitor cells promotes alpha cell production (Liu et al, 2019 ). In addition, the hypermethylation of CpG islands can reduce the expression of HNF4α gene and affect the differentiation of pancreatic β cells (Gilbert and Liu, 2012 ).…”
Section: Effects Of Dna Methylation On β Cell Differentiation and Funmentioning
confidence: 99%
“…Several studies have provided evidence to support that the development and heterogeneity of EP cells are regulated at the chromatin level (Scavuzzo et al, 2018;Yu et al, 2018;Liu et al, 2019). Our work has uncovered a regulatory role of the histone demethylase Jmjd3 (also known as Kdm6b) during the EP cell transition (Yu et al, 2018).…”
Section: Differentiation and Heterogeneity Of Epsmentioning
confidence: 56%
“…Using scRNA-seq, we found that Jmjd3 only affects the efficiency of the cell fate transition from Ngn3-GFP low to Ngn3-GFP high but does not alter the transcriptomes and developmental pathways of Ngn3 high cells (Yu et al, 2018). Liu and colleagues have proposed that the EPs are transcriptionally uniform but epigenetically distinct (Liu et al, 2019). Using scRNAseq, the authors have shown that mouse Ngn3 + cells heterogeneously express Myt1, which encodes a TF involved in regulating endocrine islet cell differentiation and function (Wang et al, 2007(Wang et al, , 2008.…”
Section: Differentiation and Heterogeneity Of Epsmentioning
confidence: 98%